WEB CONTENT ON THE PHENOMENON OF REPETITION OF QURANIC STORIES AND THEIR ARTISTIC IMPACT - Yousef A. Baker, El-Ebiary; Mohamed Rady, Mohamed Elpaz Elsheakh; Walid Mohamed, Abdelrahman Mohamed; Muhamad Zhafri, Mohammad Nazmi (2020)
Availability Rules for Web Content are part of a succession of guidelines published by the World Wide Web Association for Availability Access. It consists of a set of guidelines on making web content accessible, primarily for disabled web users, but also for all web users, and also for making it easier for any web browser to display the contents of web pages, and also for improving the display of web content on mobile phones. Many laws have been issued in many countries on the basis of rules for web content in the name of availability. Therefore, this research aims to demonstrate the phenomenon of repetition in the Qur’anic story and its artistic impact, as well as its availability on Internet sites, and that this repetition requires the intended meaning and contributes directly to crystallizing the Qur’anic connotation. It has a meaning, especially in the methods of Quranic storytelling, and the importance of the research is highlighted in that it clarifies this phenomenon in great detail as one of the phenomena of the Arabic language, one of its original rules, and its technical impact, especially in the Qur’anic stories, and how it is not inserted into a verse and its Surahs, and it has a direct relationship with the intended meaning It is closely linked to the Qur’anic Surahs in which the Qur’an story is mentioned. In this research the descriptive and analytical approach, which means describing the phenomenon in a precise description and then analyzing it with a technical analysis, and explaining its impact on highlighting and crystallizing the meaning, and one of the most important results of the research: that this phenomenon One of the phenomena of the authentic Arabic language, and His wisdom, may He be glorified and exalted be He, wanted the Qur’an to be Arabic. In the Qur’an there is nothing in the language, on top of which is the phenomenon of repetition that repetition in scenes of Qur’anic storytelling was a necessity The contexts of the verses, the difference in the angle of vision, and the different intended meaning of the narrative scene, so that it is repeated, and every time it adds a new meaning, the repetition of the story confirms the belief in the hearts of the followers, deters criminals, consoles the oppressed, gives hope to the faithful, and insists on any matter of repetition that establishes it in the souls And give him a strong warning.